The influence of brand preference among UMK (Pc) student’s on purchasing behavior: a comparative Nike and Adidas - Muhammad Fariz Shahnon; Nur Emalina Shahlan; Nur Farahin Morat; Pushpanayakar Sukumaran (2016)
This research topic is “ The influence of brand preference among umk (pc) student’s on purchasing behavior: a comparative nike and adidas”. This study is focus on the generation Y, students UMK (PC) at the age around 19-24 years. Brand preference, is intimately linked to brand choice that can assist consumer decision. Branding can be the key reason to influence consumers making a purchase. This main objective of this study is to identify the key factors that influence the choice brand among UMK (PC) and to evaluate the impact of the preference point that UMK (PC) students perceive from product (sportswear). Sportswears product is one of the major worldwide brands in attire market. This student chooses Nike and Adidas because there is the worldwide dealers of sports attire and experience in production of sports merchandise. The conceptual framework, relationship between brand preference and consumer purchasing behavior.